Radiolytic Elimination of Nabumetone from Aqueous Solution: Degradation Efficiency, and Degradants’ Toxicity - Ivana Tartaro Bujak; David Klarić; Bono Lučić; Krunoslav Bojanić; Maro Bujak; Nives Galić (Molecules)
Advanced oxidation processes (AOPs), including ionizing radiation treatment, are increasingly recognized as an effective method for the degradation of pharmaceutical pollutants, including non-steroidal anti-inflammatory drugs (NSAIDs). Nabumetone (NAB), a widely used NSAID prodrug, poses an environmental risk due to its persistence in aquatic ecosystems and its potential toxicity to non-target organisms. In this study, the radiolytic degradation of NAB was investigated under different experimental conditions (dose rate, radical scavenging, pH, matrix effect), and the toxicity of its degradation products was evaluated. NAB was rapidly degraded at 300 Gy with prolonged irradiation. Mineralization of about 88% of NAB solutions was observed based on the evaluation of total organic carbon (TOC). The most efficient degradation of NAB occurred under N2O conditions, while it was retarded in the presence of thiourea. The water matrix components had a significant influence on the efficiency of degradation. In addition, the main degradation products were identified by LC-HRMS. Toxicity studies on different bacteria showed no significant impact of the NAB degradation products, while in silico predictive methods revealed their slightly increased toxicity compared to the parent compound, but considerably lower toxicity in comparison to its main active form 6-methoxy-2-naphthylacetic acid (MNA). Additionally, significantly lower toxicities are predicted for degradation products in N2O saturated solution. These results underline the importance of optimizing irradiation parameters for effective degradation and minimizing the formation of harmful by-products. Understanding all aspects of the AOP processes and the toxicological effects of the degradation products ensures effective mitigation of potential environmental and health risks of water treatment processes.